Knowledge, attitudes and practices of grandmothers related to breastfeeding: a meta-synthesis - Bárbara Helena de Brito Angelo; Cleide Maria Pontes; Gabriela Cunha Schechtman Sette; Luciana Pedrosa Leal (Universidade de São Paulo, 2020)
Objective: Evaluate the knowledge, attitudes and practices of grandmothers that support or discourage the breastfeeding process. Method: This is a meta-synthesis based on the theoretical and methodological framework of meta-ethnography developed by Noblit and Hare. A critical evaluation of the articles was conducted using the consolidated criteria for reporting qualitative research (Coreq). Primary and secondary constructs derived from the results of nine articles were grouped into a new theory, leading to tertiary constructs that were presented in a diagram based on the functionality of Sanicola's Social Network Theory. Results: Grandmothers know the benefits of breastfeeding, the importance of a special diet and proper hydration for the production of good quality milk, but report inadequacies in the treatment of breast complications and the need for breast milk complementation before the sixth month of life. These aspects were also observed: religious interference, opposition of ideas about breastfeeding, and family decisions based on the grandmother figure. Conclusion: Through knowledge, attitudes and practices, grandmothers, central figures in breastfeeding support, support their daughters and daughters-in-law in breastfeeding or discourage breastfeeding with contrary opinions and inadequate guidance.